Ultrasonic extraction of antioxidant compound in guava - Khairul Anwar, Mohamad Said (2009)
The antioxidant such as ascorbic acid (AA) in guava juice has attracted a lot of interest from the public and herbal industries because of the antioxidant can inhibit the oxidation of body cells that can lead to health problem. The work done in this research investigates the most suitable operating parameter to extract the ascorbic acid from guava using ultrasonic extraction method. Different parameter volume of solvent which is ethanol at 30ml, 50ml, 200ml and 250ml. After determine the best solvent volume were investigated the experiments were conducted using different ultrasonic power at 150W, 200W, 250W and 300W after the determination of the best solvent volume. The sonication time was set at 20min, 30min, 50min and 60min. The extraction yields were analyzed using High Performance Liquid Chromatography system (HPLC). Result obtained revealed that 250 ml of ethanol, ultrasonic power of 300W and 20 minutes sonication time produce the highest yield of ascorbic acid. The extracted amount of ascorbic acid was 4.3150 mg/L. Therefore, these parameters can be concluded as the most optimum operating parameters in extracting ascorbic acid from guava using ultrasonic extraction method.